2019
DOI: 10.1002/fam.2755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flat roof–integrated solar photovoltaic installation mode on building fire safety

Abstract: Summary This paper quantifies experimentally the fire‐induced reradiation to roof surface created by flame extension on the back of the flat roof–integrated photovoltaic (PV) array. A gas burner underneath the tilted PV panels was employed as the fire source. The effects of the PV tilt angle, distance from PV panel to roof, and fire heat release rate (HRR) were investigated. The flame extension geometries and flame reradiation heat flux distribution were recorded. The results show that the flame extension leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…As the angle of inclination varies across different installations, a fundamental analysis of flame spread below a horizontal panel is essential before introducing the influence of inclinations. This is supported by previous research which revealed that the smallest gap distance is expected to be most critical from a fire safety point of view due to increased heat flux [10], [27]. Thus, the current experiments are configured to form an understanding on how a non-combustible panel affect the initial stages of flame spread and subsequently compare these results to the influence of a PV module.…”
Section: Introductionsupporting
confidence: 69%
“…As the angle of inclination varies across different installations, a fundamental analysis of flame spread below a horizontal panel is essential before introducing the influence of inclinations. This is supported by previous research which revealed that the smallest gap distance is expected to be most critical from a fire safety point of view due to increased heat flux [10], [27]. Thus, the current experiments are configured to form an understanding on how a non-combustible panel affect the initial stages of flame spread and subsequently compare these results to the influence of a PV module.…”
Section: Introductionsupporting
confidence: 69%
“…They explain that electric shock risks may occur from vital electrical PV components coming into contact with workers. Since PV systems are challenging to de-energize once energized and exposed to sunlight (Levins, 1986; Wybo, (2) Utilizing fire-resistant material during installations (Cancelliere et al , Ju et al , 2019) (3) Ground or insulate dead metal parts, implement safety such as ground fault and bypass diodes (Levins, 1986) Design alleys in a PY system to aid circulation (Wu et al, 2020;Wybo , 2013) design frangible structures to make panel fol dab le in case of shock emergency (Wybo, 2013) (7) Increasing the PY tilt angle and panel-roof distance to reduce flame propagation (Ju et al , 2019;Kristensen et al , 2021) (8) Utilize refractory glass and Type II J-box design (Huang et al ,20 I 8) (9) PY module backsheet fire-resistant design (Cancelliere et al , 2014) ( I 0) Strategic placement of fire fighting equipment across the plant and in vehicles, clearing of fire breaks around site boundary (Guerin, 2017) ( 11) Arc Fault detection techniques and algorithms (Wu et al , 2020;Onrran et al , 2020;Lu et al , 2018) (I) Unacclimatized workers with a work intensity of 400 kcal/h (heavy work) need to rest for 75% of each hour.…”
Section: Electrical and Fire Hazardsmentioning
confidence: 99%
“…The remaining references focus on fire risks concerning rooftop PV installations. For example, multiple articles studied the effect of PV tilt angle and panel-roof distance on reducing the potential of fire outbreaks associated with PV installations (Ju et al, 2019;Kristensen et al, 2021;Kristensen & Jomaas, 2018). At the same time, other studies focused on improving the junction box design (Huang et al , 2018) or module backsheet design to reduce fire risks (Cancelliere et al, 2014).…”
Section: Electrical and Fire Hazardsmentioning
confidence: 99%
“…The preventive actions include array recombination and detection algorithm research. The studies [40][41][42][43][44][45][46][47][48][49][50] illustrate the reconfiguration of PV modules or PV arrays, and the studies introduce algorithm to detect the faulty PV modules.…”
Section: Solutions To Prevent Pv Fire Accidentsmentioning
confidence: 99%
“…When the module is arranged horizontally, the purlins are arranged vertically as shown in Figure 11. In this case, due to the chimney effect, the fire spreads faster than arrays with vertically arranged components [43][44][45].…”
Section: Figure 10 Dust Deposition On a Pv Arraymentioning
confidence: 99%